Assessment of the neuropathic component in a chronic low back pain syndrome - Vukojević, Zoran; Dominović Kovačević, Aleksandra; Perić, Stojan; Božović, Ivo; Grgić, Sanja; Basta, Ivana; Lavrnić, Dragana (Vojnosanitetski pregled, 2022)
Background/Aim. Chronic low back pain syndrome (CLBPS) is the most common cause of functional disability and loss of working ability in developed countries. Some research shows that neuropathic pain (NP) is present in almost 50% of patients with CLPBS. The aim of this study was to determine the characteristics of NP and its impact on quality of life (QoL) in patients with CLBPS. Methods. Patients were tested using three questionnaires for NP: Pain Detect Questionnaire, Leeds Assessment of Neuropathic Symptoms and Signs, and Douleur Neuropathique 4 questions. Thirty-two patients diagnosed with NP based on current clinical criteria and with positive results for NP on all three NP questionnaires formed an experimental group. A control group consisted of 32 patients with CLBPS who did not fulfill clinical criteria for NP and were negative for NP on all three questionnaires. Hamilton depression and anxiety rating scales (Ham-D and Ham-A, respectively) and Short Form (SF)-36 questionnaire were also applied. Results. According to magnetic resonance imaging (MRI), disc herniation was typically detected in the experimental group, while degenerative changes were commonly found in the control group. Patients from the experimental group had significantly greater intensity of pain, pain radiation in the legs, and the pain was usually presented as episodes of sudden attacks with mild pain between them. The most distinctive features of NP were allodynia, electric shock sensation, and hypoesthesia to prick. Patients from the experimental group also had significantly higher depression and anxiety scores, as well as worse QoL compared to the control group, especially in mental domains. Predictors of worse QoL in the patients with CLBPS were a higher level of anxiety and depression. Conclusion. The presence of allodynia, electric shock-like sensations, and hypoesthesia to prick in patients with CLBPS suggest NP. CLBPS patients with NP had worse scores in mental domains of QoL compared to CLPBS patients without NP.
Keywords: anxiety; back pain; depression; neuralgia; quality of life